Distribution and environmental associations of invasive freshwater Pomacea snails in Peninsular Malaysia - Hah, Huai En *; Liew, Thor Seng; Suganiya, Rama Rao *; Yow, Yoon Yen *; Shyamala, Ratnayeke * (Springer, 2021)
Freshwater habitats represent one of the most important ecosystems for sustaining terrestrial biodiversity and human societies, but are particularly vulnerable to the effects of pollution and species invasions. Two highly invasive species of freshwater snail, Pomacea canaliculata and P. maculata, occur in Malaysia, but apart from their impacts on rice agriculture, little information exists about their distribution and associated environmental factors. We investigated the distribution of these two species and associated environmental gradients by surveying 550 quadrats at 108 geographic locations in Malaysia and measuring selected water parameters, including the species richness of co-occurring gastropods. Sampling locations comprised five different habitats: rivers and streams, lakes and ponds, reservoirs, waterfalls, and rice fields. We used DNA sequencing and rapid multiplex PCR assay with mitochondrial DNA markers to assign species identity to snails from 73% of locations where they occurred. We used ordination analyses and generalized linear models to evaluate associations between the presence of Pomacea and aquatic covariates. We found Pomacea in 267 sampling quadrats and 59 geographic locations. P. canaliculata and P. maculata composed 63% and 37%, respectively, of 647 snails identified to species. Both species coexisted in at least 13 locations and occurred in all surveyed habitats except waterfalls, but P. canaliculata was more strongly associated with rice fields than P. maculata. Ordination analysis confirmed strong interspecific similarity in environmental parameters. The probability of presence of Pomacea as a group increased with greater gastropod species richness, higher temperature, sodium, and pH, and decreasing dissolved oxygen. A substantial fraction of freshwater habitats in the peninsula appear susceptible to invasion. This study is the first to report environmental associations of Pomacea spp in southeast Asia, but only 260 individuals (< 50%) were identified to species using sequencing. Thus, our conclusions related to species identity should be viewed conservatively.